PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DENGAN TEMA KEGIATAN SEHARI-HARI MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS III SDN 02 BATANG GASAN - Gadijah Gadijah (STKIP Pesisir Selatan, 2016)
ABSTRACTBased on the acquisition of learning outcomes of Class III students at SDN 02 Batang Gasan in thematic learning with the theme of daily activities it was found that many student learning outcomes were still incomplete. The purpose of this study was to describe and obtain information about improving student learning outcomes in thematic learning with the theme of daily activities through an instant learning assessment model with media choose number in Class III SDN 02 Batang Gasan. This research is classroom action research with research procedures covering planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 31 students of Class III SDN 02 Batang Gasan. The research data was collected using a test sheet. Data were analyzed using percentages. The results of the study and discussion show that the learning model of Instant Assessment learning model using choose number media can improve student learning outcomes in thematic learning with the theme of daily activities in Class III SDN 02 Batang Gasan. Student learning outcomes in the first cycle were 72.90 increased to 83.87 with an increase of 10.97%.